Differences in Perceived Value of Team Projects and Learning Styles of Accounting and Marketing Students - Madupu, Vivek; Gunderson, Konrad (Journal of Accounting, Business and Management (JABM), 2024)
This study investigates the learning styles of accounting and marketing students and, whether specific learning styles favour team projects. Based on a student sample from a Mid-Western University in the USA, our research indicates that marketing students are more active and visual learners than accounting students. In contrast, accounting students are more reflective, sensing, and sequential learners compared to marketing students. Our study also indicates that active learners and visual learners perceive higher value from participating in team projects. Overall, it appears that marketing students value team projects more than accounting Students. Our study also suggests that team projects are not for everybody. In general, marketing students value team projects more. When teaching an introductory marketing course, which is more likely to be a mix of students with different learning styles, educators may give team projects along with individual projects.